KETIDAK BERFUNGSIAN KUD âKOSKOPABOâ (Kasus KUD âKOSKOPABOâ Di Nagari Bonjol Kec. Koto Besar Kab. Dharmasraya) - Yulita, Sesra - (Pendidikan Sosiologi, 2014)
In Nagari Koto subdistrict Great snag Dharmasraya there is a village cooperatives called "KOSKOPABO" which means Great Koto Padang Lagerstroemia and snag. The role of the board in promoting cooperative efforts do not go according to the decision of the meeting of members, for the training of members of farmer groups not performing as it should, and information among members of farmer groups are not going well, so that the activities of the cooperative is not running as expected. The theory used in this study is the theory of structural functionalism. This theory is the idea of a social life as a system, a network of different sections, explaining part of the structure. This research is categorized into types of qualitative research approaches. This type of research used in this research is descriptive. The informants in this study is the caretaker of KUD "KOSKOPABO", chairman of the group, and members of KUD "KOSKOPABO" in Nagari Koto subdistrict Great snag Dharmasraya. Data to be collected in this study are primary data obtained through the data collection methods such as interviews. The unit of analysis is the group with the analysis of the data comprising the steps of reduction, data presentation / analysis of data, and drawing conclusions. The results of the study of the dysfunctional KUD "KOSKOPABO" in the welfare of members of the group ( in the case of Nagari Koto subdistrict Great snag Dharmasraya ), can be explained as follows: 1) The Board does not seek the good of activities to be executed by their members, so that the program of work that has previously been made not run well. It was evident from the activities that are not operated by the cooperative. 2) Training of members of farmer groups not performing as it should, due to a lack of planning and lack of clarity about the division of tasks assigned to each group leader. 3) There is inequality in the distribution of fertilizers to all farmers groups led to economic inequality groups.